DEVELOPMENT OF THE WORLD NICKEL MARKET UNDER THE INFLUENCE OF INNOVATIVE TECHNOLOGIES - M. Antropova (Вестник университета)
The aim of the study is to identify methods of application of additive technologies based on powder metallurgy. The technologies of 3D printing based on metal powders with AM-machines (additive manufacturing) with nickel are discussed. The theoretical substantiation of the main perspective directions of using of artificial intelligence technologies in metallurgy has been maked. It is proposed to develop methods for standardization of raw materials for additive technologies in metals. The modern tendencies of the world economy development which indicate the transformation of the world nickel market under the influence of innovative technologies has been analyzed.